DIAGNOSIS SYSTEM IN CHICKEN DISEASE USING FORWARD CHAINING METHOD - Annisaa Utami; Faisal Dharma Adhinata; Yaqutina Marjani Santosa (Jurnal Teknik Informatika (Jutif), 2022)
Chickens are animals that are mostly kept by the community both on a large and small scale traditionally. Because the population is large, the disease is also more complex, from mild disease to diseases that can be transmitted to humans so that it can cause death such as bird flu. Diseases in chickens such as Newcastle Disease (ND), Infectious Bronchitis (IB), Gumboro Disease and Flu. Problems about chicken disease faced requires a system to help in diagnosing diseases in chickens. Expert system is a system in which a variety of knowledge comes from an expert so that users can consult. Forward Chaining method is a method of searching or forward-looking where tracking begins with information that da and combine rules to produce an expected conclusion or goal. The study used 9 disease data, 34 symptom data and 20 cases of chicken disease. The results of the accuracy test get a value of 90%. The purpose of this study is: diagnosing chicken disease as a first step to applying artificial intelligence in the medical world, designing and applying systems. Based on the data, it can be concluded that the protythepe expert system by implementing the Forward Chaining Method can help farmers and chicken owners in diagnosing chicken diseases.